The moon and serpent bumper book of magic - Moore, Alan, 1953-; Moore, Steve, 1949-2014 (Top Shelf Productions : Knockabout Comics, 2024)
"The most acclaimed writer in comics history, Alan Moore, joins his late mentor Steve Moore (no relation) for one last graphic grimoire: a sprawling and stunning introduction to magic in all its timeless forms, brought to life by six wondrous and whimsical artists. Splendid news for enquiring minds, and guaranteed salvation for humanity! Messrs. Steve and Alan Moore, proprietors of the celebrated Moon and Serpent Grand Egyptian Theatre of Marvels (sorcery by appointment since circa 150 AD), have produced a clear and practical grimoire of the occult sciences that offers endless necromantic fun for all the family. Exquisitely illuminated by a host of adepts including Kevin O'Neill, John Coulthart, Steve Parkhouse, Rick Veitch, Melinda Gebbie, and Ben Wickey, this marvellous and unprecedented tome promises to provide all that the reader could conceivably need in order to commence a fulfilling new career as a diabolist. Its contents include profusely illustrated instructional essays upon this ancient sect's theories of magic, notably the key dissertation "Adventures in Thinking," which gives reliable advice as to how entry into the world of magic may be readily achieved. Further to this, a number of "Rainy Day" activity pages present lively and entertaining things to do once the magical state has been attained, including such popular pastimes as divination, etheric travel, and the conjuring of a colourful multitude of spirits, deities, dead people, and infernal entities from the pit, all of whom are sure to become your new best friends. Also contained within this extravagant compendium of thaumaturgic lore is a history of magic from the last ice age to the present day, told in a series of easy-to-absorb pictorial biographies of fifty great enchanters and complemented by a variety of picture stories depicting events ranging from the Palaeolithic origins of art, magic, language, and consciousness to the rib-tickling comedy exploits of Moon and Serpent founder Alexander the False Prophet ("He's fun, he's fake, he's got a talking snake!"). In addition to these manifold delights, the adventurous reader will also discover a series of helpful travel guides to mind-wrenching alien dimensions that are within comfortable walking distance, as well as profiles of the many quaint local inhabitants that one might bump into at these exotic resorts. A full range of entertainments will be provided, encompassing such diverse novelties and pursuits as a lavishly decorated, decadent pulp tale of occult adventure recounted in the serial form. Completing this almost-unimaginable treasure trove is a lengthy thesis revealing the ultimate meaning of both the Moon and the Serpent in a manner that makes transparent the much-obscured secret of magic, happiness, sex, creativity, and the known Universe, while at the same time explaining why these lunar and ophidian symbols feature so prominently in the order's peculiar name. (Manufacturer's disclaimer: This edition does not, however, reveal why the titular cabal of magicians consider themselves to be either grand or Egyptian. Let the buyer beware.) A colossal and audacious publishing triumph of three hundred and fifty-two pages, beautifully produced in the finest tradition of educational literature for young people, The Moon and Serpent Bumper Book of Magic will transform your lives, your reality, and any spare lead that you happen to have lying around into the purest and most radiant gold."--provided by publisher.